Obstacles of political party development in Iran - Asayeseh, Hossien; Ab. Halim, Adlina; Shojaei, Seyedeh Nosrat (Marsland Press, 2010)
The political party is a means of connecting the political process with society and it helps to improve the political system. Oldness of political party development in Iran reaches almost a century but political parties could not have an important role in Iranian political system. This paper looks at obstacles of political party development in Iran and describes obstacles such as; fund, electoral system, political culture, Rentier state, power centralization, civil society and separation between elite groups and masses. In this article we examine how these hindrances impede of party development process in Iran.